Photooxidation of Some Organic Sulfides under UV Light Irradiation Using Titanium Dioxide Photocatalyst - Hakimeh Vosooghian; Mohammad Hossein Habibi (International Journal of Photoenergy)
The photocatalytic oxidation of three organic sulfide compounds (thioethers); methyl phenyl sulfide (MPS), benzyl phenyl sulfide (BPS), and diphenyl sulfide (dPS) using titanium dioxide (TiO2) photocatalyst suspension under UV light irradiation in aqueous-acetonitrilic (5/95), was studied. Three types of experiments were carried out: (a) the solution was eliminated from atmospheric oxygen by a flow of argon before irradiation, (b) the solution was irradiated with continuous bubbling of oxygen, and (c) the irradiation was carried out at neutral atmospheric oxygen conditions. Results showed that the process will proceed in the presence of pure oxygen much better than atmospheric oxygen or in the absence of oxygen. In fact, no detectable products were observed in the presence of atmospheric oxygen or argon flux. Besides the main products such as methyl phenyl sulfoxide, benzyl phenyl sulfoxide, diphenyl sulfoxide, diphenyl disulfide, benzaldehyde, phenyl propyl sulfide, and n-buthyl phenyl sulfide, trace concentrations of dibenzyl, biphenyl, thiophenol, benzyl alcohol, benzene, benzyl phenyl sulfone, diphenyl sulfone, and methyl phenyl sulfone were detected. Thus in summary, this study provides an example of specific, controlled oxidative chemistry in organic substrates adsorbed on photoactivated TiO2 surface.